Mapping of Landslide Areas Using Geographic Information Systems In Kebonharjo Kulon Progo Regency - Pramudya Bagas Utama (Universitas Medan Area, 2022)
Indonesia is a country that is surrounded by a ring of volcanoes or commonly known as a ring of fire, the implication is there are many disaster caused by tectonic processes such as collisions between plates, earthquakes, and landslides. Landslides are disaster that often occur in Indonesia, especially the study area in Kebonharjo Village. Disaster events cause damage to both the physical and non-physical environment. The mapping of the area used the Geographic Information System method based on actual data provided by the Regional Disaster Management Agency of Kulon Progo Regency in the form of hamlet areas that are prone to landslides and areas that occur landslide disaster. Other data is data from the Geospatial Information Agency to facilitate direct observation and mapping in the research field. The method used is a survey method with a quantitative and qualitative analysis approach. Qualitative analysis was carried out using the method of analyzing the topography and geomorphology of the research area. Quantitative analysis was carried out based on landforms classified with aspects of slope, rock type, soil type, and rainfall intensity. The results of the analysis of these data will produce a landslide hazard map in the research area as a reference that can be used by the local government to determine appropriate environmental management strategies and policies in Kebonharjo Village.